2014
DOI: 10.1097/mbc.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inhospital prognosis in acute pulmonary embolism

Abstract: The assessment of commonly available demographic, clinical, and easily calculable investigational parameters instead of the conventional complicated indices for prognosis in acute pulmonary embolism may help in triage in a simple and cost-effective way. Clinical, demographic, and investigational parameters were collected and utilized for the assessment of inhospital prognosis of acute pulmonary embolism in 200 consecutive patients admitted to our institute. Overall mortality was 18% and poor outcome at dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
3
21
0
1
Order By: Relevance
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies (4898 patients) reported data on in-hospital mortality. [4][5][6][7]9,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Several ECG features were meta-analyzed for this outcome ( Table 2). Figure 2 shows 4 sample forest plots for the association between in-hospital mortality and each of the following ECG findings: S1Q3T3, any RBBB, TWI in precordial leads, and TWI in precordial or inferior leads.…”
Section: In-hospital Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…STDV is considered a common, but non--specific, ECG manifestation in patients with APE by some authors [11,12]. However, the literature suggests that the distribution of STDV has consistent regularity and mechanisms [6][7][8][9][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%